Factors Associated with Diabetes Mellitus among Adults Aged ≥ 25 Years in DKI Jakarta: Analysis of the 2023 Indonesian Health Survey - Thahara, Annisa Ryan; Iriani, Dewi Utami (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: The global prevalence of diabetes mellitus (DM) continues to rise and is projected to increase significantly by 2045. In Indonesia, DKI Jakarta reports the highest prevalence of DM. This study aimed to examine factors associated with DM among adults aged ≥ 25 years in DKI Jakarta using data from the 2023 Indonesian Health Survey. Methods: A cross-sectional study was conducted using secondary data from the 2023 Indonesian Health Survey, which employed a stratified multistage sampling design. A total of 6,185 respondents aged ≥ 25 years residing in DKI Jakarta were included. Data were collected in 2023 and analysed from January to July 2025. Multiple logistic regression analysis was performed to estimate adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for factors associated with DM. Results: Significant risk factors for DM among adults aged ≥ 25 years in DKI Jakarta included age (OR=21.99; 95% CI: 13.13–36.85; p<0.001), sex (OR=1.63; 95% CI: 1.23–2.15; p=0.001), educational level (OR=1.86; 95% CI: 1.20–2.90; p<0.001), depression (OR=3.71; 95% CI: 1.81–7.58; p<0.001), and a hystory of hypertension (OR=5.05; 95% CI: 3.83–6.66; p<0.001). Based on multivariable analysis, older age was the most strongly associated factor (aOR = 16.081; 95% CI: 9.24–27.98; p<0.001). Conclusions: Several sociodemographic and health-related factors were associated with DM among adults in DKI Jakarta. Strengthening diabetes prevention and control efforts through the Posbindu PTM and GERMAS programmes by the DKI Jakarta Health Office is warranted.